PENGEMBANGAN MEDIA E-LKPD INTERAKTIF BERBASIS LIVEWORKSHEET MATA PELAJARAN IPAS MATERI PERUBAHAN WUJUD BENDA SISWA KELAS IV SD GUGUS II KUBUTAMBAHAN - Kadek Tiara Yuli Antari; I Nyoman Pancaria; Putu Eka Sastrika Ayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an interactive E-LKPD based on liveworksheets for the subject of Natural and Social Sciences (IPAS), specifically on the topic of changes in the state of matter for fourth-grade students at SD Gugus II Kubutambahan District. This research is a Research and Development (R&D) study using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study were fourth-grade teachers and students in the selected elementary schools. The results showed that the developed E-LKPD media obtained very high validity levels, with material expert validation of 0.90, media expert validation of 0.94, and language expert validation of 0.91. In addition, the practicality test results showed very positive responses, with 97% from teachers and 96% from students, categorized as very practical. These results indicate that the developed media is feasible for use in the learning process. In conclusion, the interactive E-LKPD based on Liveworksheets is valid and practical to be used as a learning media to help students understand the concept of changes in the state of matter in a more engaging, interactive, and meaningful way